Model for Innovative Use of Ziswaf Funds to Enhance the Competitiveness of Microeconomic Actors in the Digital Economy - Agung Rizkiyan; Dhaisya Dea Maretha; Revalina Melati Ayuningtyas; Zulfa Dela Octavia (Journal of Islamic Digital Economic and Finance, 2025)
Introduction: Digital transformation over the past decade has opened significant opportunities and challenges for optimizing the utilization of Zakat, Infaq, Sedekah, and Wakaf (ZISWAF) funds as instruments of Islamic social finance. In Indonesia, micro-economy actors still face various obstacles, such as limited access to capital, low financial and digital literacy, and limited market access. Objective: This study aims to develop an innovative model for the digital utilization of ZISWAF funds to enhance the competitiveness of microeconomic actors. Method: A qualitative approach with a descriptive-analytical design is used, informed by a literature review and analysis of secondary data from various institutional reports and prior studies. Results: The study findings indicate that the utilization of ZISWAF is still dominated by a consumptive pattern, even though productive zakat has been shown to increase beneficiaries’ income by up to 58% per year. Furthermore, digitalization has been shown to double MSMEs' revenue, yet technology adoption rates remain low. Therefore, this study proposes an integrative model based on a digital platform that encompasses access to financing, online training, digital marketing, and a data-driven monitoring system. Implication: This study confirms that the digital transformation of ZISWAF can serve as an effective strategy to promote inclusive, sustainable microeconomic empowerment that aligns with the principles of maqashid syariah.